2014
DOI: 10.1186/s40662-014-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Practical issues concerning tear protein assays in dry eye

Abstract: Dry eye is a common clinical condition diagnosed by cumulative evidence of symptoms and signs. Many new treatments in dry eye are either expensive, invasive, have potential for side effects, or are not easily accessible. In severe dry eye, the ideal modality of treatment to begin with is often not clear as specific molecular disturbances are not evident from just examination of clinical manifestations. Assessing the effects of ongoing treatment is not straight forward since there is lack of agreement between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 122 publications
(165 reference statements)
1
29
0
18
Order By: Relevance
“…It is possible that this phenomenon is due to the nature of most non-SS DE patients recruited at the Roski Eye Institute corneal clinic, a tertiary care clinic, who may represent a different spectrum of dry eye disease than populations in previous studies. Alternatively, differences in tear collection techniques, the use of glass capillaries versus elution from Schirmer’s strips or even the choice of an anesthetised versus an unanesthetised Schirmer’s test may also play a role 48 . It is important to note that analysis techniques have varied across studies from radial immunodiffusion to ELISA-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this phenomenon is due to the nature of most non-SS DE patients recruited at the Roski Eye Institute corneal clinic, a tertiary care clinic, who may represent a different spectrum of dry eye disease than populations in previous studies. Alternatively, differences in tear collection techniques, the use of glass capillaries versus elution from Schirmer’s strips or even the choice of an anesthetised versus an unanesthetised Schirmer’s test may also play a role 48 . It is important to note that analysis techniques have varied across studies from radial immunodiffusion to ELISA-based assays.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have shown differences in several tear molecules in DED patients compared to healthy subjects, or among the different types of DED. A number of reviews on the use of tears as a source of biomarkers have been published to date, including for non-ocular diseases [ 23 25 ] and in reviews specifically dedicated to DED [ 26 29 ].…”
Section: Tear Fluid Analysis In Ocular Diseasementioning
confidence: 99%
“…Significantly increased expression of IL-1α, IL-6, IL-8, TNF-α, and TGF-β1 was found in conjunctiva epithelium of SS patients when compared to healthy controls [ 15 ]. Other studies demonstrate that IL-1, IL-6, IL-8, TNF-α, interferon-γ (IFN-γ) and IL-17 are highly expressed in SS patient tears relative to non-SS patients [ 16 , 17 , 18 , 19 ], suggesting that elevated pro-inflammatory cytokines may be related to disease progression in SS patients. In this study, we specifically hypothesized that tear CTSS may directly increase pro-inflammatory cytokine expression in human corneal epithelial cells, an effect that may contribute to ocular surface inflammation in SS.…”
Section: Introductionmentioning
confidence: 99%